2020
DOI: 10.34202/imanensi.5.1.2020.53-60
|View full text |Cite
|
Sign up to set email alerts
|

Determinan ketepatan waktu pelaporan keuangan perusahaan pertambangan indonesia

Abstract: Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh debt to equity ratio profltabilitas, pergantian auditor dan ukuran perusahaan terhadap ketepatan waktu pelaporan keuangan. Perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia pada tahun 2014-2017 dipilih sebagai populasi penelitian. Metode pengambilan sampel adalah purposive sampling. Data dianalisis dengan regresi logistik. Hasil penelitian menunjukkan bahwa secara parsial, profitabilitas dan pergantian    auditor memengaruhi ketepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…So it can be concluded that Ha4 is accepted, meaning that firm size has a significant positive effect on the timeliness of financial statements submission. The results of this study are in line with research conducted by Pradipta and Suryono (2017); Utami and Yennisa (2017); Ferdina and Wirama (2017); Sanjaya and Wirawati (2016) but contrary to the results of a study conducted by Tifanny, Rahayu and Yustien (2020).…”
Section: Parameter Estimation and Interpretationsupporting
confidence: 85%
“…So it can be concluded that Ha4 is accepted, meaning that firm size has a significant positive effect on the timeliness of financial statements submission. The results of this study are in line with research conducted by Pradipta and Suryono (2017); Utami and Yennisa (2017); Ferdina and Wirama (2017); Sanjaya and Wirawati (2016) but contrary to the results of a study conducted by Tifanny, Rahayu and Yustien (2020).…”
Section: Parameter Estimation and Interpretationsupporting
confidence: 85%
“…Internal factors (voluntary) are management decisions that replace auditors before the obligation of audit rotation or auditors who resign, and external factors are the obligation of audit rotation according to government regulations (mandatory). Changing auditors will encourage companies to present financial reports better than when the company was still being audited by the previous auditor (Tifanny et al, 2020). The replacement of the auditor is carried out to maintain the independence and objectivity of the auditor.…”
Section: Auditor Switchingmentioning
confidence: 99%
“…Consequently, timeliness represents a significant challenge in the timely publication of financial statements. To measure this variable, the number of days is calculated by counting the duration between the company's book closing date and the date stated in the independent auditor's report (Tifanny et al, 2020).…”
Section: Audit Delaymentioning
confidence: 99%